Communication Elements In The Suratul Yusuf - Taofeeq Hamzat Adebiy; Adebayo Rafiu Adesiji; Rajiu Wasiu Kehinde; Oshin Oluwole Bamidele; Siti Suriani Othman (Universiti Sains Islam Malaysia, 2024)
Abqari vol. 4, 2014